Case Study of Standardized Nutrition Care Process in Taekwondo Kyorugi Athletes 49 kg - Tommy Gantohe; Nazhif Gifari; Mertien Sa’pang; Irtya Qiyamulail (STKIP Muhammadiyah Kuningan, 2022)
Taekwondo is a fighting sport that is part of international sports competitions. The existence of a weight-based class system aims to ensure a balance of strength, body size and range of motion between athletes who will compete. The class system based on body weight causes athletes to try to achieve the appropriate weight for the competition class before the match. An extreme and not adequately monitored weight loss program can affect an athlete's performance and even endanger the athlete's health. This case study aims to see the impact of providing nutritional intervention in the PON preparation period on changes in athletes' weight. The process of standardized nutrition care to help taekwondo athletes achieve body weight according to competing classes is gradual, safe and minimizes risk. The method used in this research is a case study with several subjects, as many as one athlete. Based on the results of this case study, it is known that giving a low-calorie diet for ten days of intervention showed an effect on the weight loss of athletes. At the end of the intervention period, there was a weight loss of 1.5 kg.